2019
DOI: 10.1088/1674-4926/40/7/071906
|View full text |Cite
|
Sign up to set email alerts
|

III–V compounds as single photon emitters

Abstract: Single-photon emitters (SPEs) are one of the key components in quantum information applications. The ideal SPEs emit a single photon or a photon-pair on demand, with high purity and distinguishability. SPEs can also be integrated in photonic circuits for scalable quantum communication and quantum computer systems. Quantum dots made from III-V compounds such as InGaAs or GaN have been found to be particularly attractive SPE sources due to their well studied optical performance and state of the art industrial fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 142 publications
1
4
0
Order By: Relevance
“…We found that 50% of our emitters show a very good single photon emission, with g (2) (τ) < 0.2. This result shows a single photon emission quality comparable with other room temperature single photons emitters such as CdS/CdSe dot in rod, 49 InGaN quantum dots, 50 and NV defects in nanodiamonds. 51 We performed a statistical analysis of the g (2) (0) as a function of the central emission wavelength, shown in Figure 6b.…”
Section: Acs Photonicssupporting
confidence: 69%
“…We found that 50% of our emitters show a very good single photon emission, with g (2) (τ) < 0.2. This result shows a single photon emission quality comparable with other room temperature single photons emitters such as CdS/CdSe dot in rod, 49 InGaN quantum dots, 50 and NV defects in nanodiamonds. 51 We performed a statistical analysis of the g (2) (0) as a function of the central emission wavelength, shown in Figure 6b.…”
Section: Acs Photonicssupporting
confidence: 69%
“…Notably, the strong antibunching of Cs 0.2 FA 0.8 PbBr 3 quantum dots indicates single photon emission quality comparable or even higher than room temperature single photon emitters like NV defect centers in diamonds 46 or III−V semiconductor quantum dots. 47 This opens new opportunities for integration of mixed-cation perovskite quantum dots into existing quantum photonic platforms.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Weaker dephasing can also be tailored either via a reduction in the QD size 17 , 18 or the absence of any built-in electric field in zinc-blende III-N QDs 19 , 20 . In addition, III-N QDs remain of utmost relevance for room temperature (RT) SPE applications, where their state of the art III-arsenide counterparts are inoperable 21 . III-N QDs may be particularly well suited for quantum operations that do not require photon indistinguishability 2 , 22 , such as quantum-key distribution 23 , 24 , quantum imaging 25 or quantum metrology 26 .…”
Section: Introductionmentioning
confidence: 99%